A rabbit eye model for in vivo transformation of progenetic metacercariae of Clinostomum complanatum into ovigerous adult worms. Issue 1 (March 2014) - Rizvi, A.; Zaidi, Z.A.; Alam, M.M.; Zafar, A.; Shareef, P.A.A.; Saifullah, M.K.; Saleemuddin, M.; Abidi, S.M.A.
Abstract Clinostomum complanatum is a digenetic trematode that causes yellow grub disease in some fish species and also shows zoonotic potential by sporadically infecting humans. In this study, progenetic metacercariae of C. complanatum were obtained from the fish Trichogaster fasciatus, and were aseptically placed in conjunctival incisions made in the superior and inferior fornices of the eye of rabbits, which served as the experimental hosts. Worms were harvested without necropsy of the host on days 4 and 8 post infection, to observe in vivo transformation of the progenetic metacercariae into ovigerous adult worms. The worms appeared to cause minimal damage to the host although they were tenaciously attached. In vivo maturation was evident by the development of the vitellaria, enlargement of gonads, the presence of a large number of shelled eggs in a distended uterus and ramifications of the intestinal caeca. Obtaining mature ovigerous worms without sacrificing the host clearly gives the rabbit eye model an advantage over those described previously. Due to the relative advantage of the short time required for maturation and the prolific egg production by C. complanatum, it is suggested that this host–parasite system could be used as an excellent model for classroom teaching of trematode biology and to investigate the cues involved in in vivo transformation and host–parasite interactions.